Managing the Learning Process to Cultivate Disciplinary Behavior in Early Childhood Education - Baini Baini; N. Dede Khoeriah Khoeriah (CV. Media Digital Publikasi Indonesia, 2026)
Cultivating disciplined behavior is a cornerstone of early childhood education, yet educators often lack the managerial competence to implement integrated learning that effectively fosters this trait. This study was prompted by the need for a systematic learning management approach to address inconsistencies in fostering student discipline. The purpose of this research is to analyze how learning management, guided by Deming’s Plan-Do-Check-Act (PDCA) cycle, can enhance the disciplinary behavior and socio-emotional development of young children. This study employed a qualitative approach with a descriptive, multiple-case study design conducted at two inclusive early childhood centers in East Jakarta: PAUD Pelita Hati and TK Sa’adatuddarain. Data were collected through in-depth interviews with teachers and parents, direct observation of classroom activities, and analysis of documentation such as daily lesson plans. Data analysis followed the interactive model of Miles and Huberman. The findings demonstrate that a systematic management cycle effectively cultivated discipline. Planning involved creating structured daily plans (RPPH) that embedded character-based objectives. Implementation utilized varied, engaging methods, with a consistent focus on modeling, positive reinforcement, and habituation of rules. Evaluation was conducted through continuous formative and summative assessments. The follow-up phase used these evaluation data to refine strategies and provide differentiated support, creating a continuous improvement loop. This study concludes that the systematic management of the learning process, grounded in the PDCA cycle, is a highly effective framework for enhancing disciplinary behavior in young children. The consistent application of planning, implementation, evaluation, and adjustment fosters an environment where children internalize rules, manage emotions, and develop a strong sense of responsibility. This research provides a replicable model for early childhood educators to transform discipline from a reactive measure into a proactively managed component of holistic child development.